Heat-sensitive moxibustion self-administration in patients in the community with primary hypertension: A protocol for a multi-center, pragmatic, non-randomized trial. Issue 38 (18th September 2020) - Zhou, Xu; Wu, Qingni; Zhang, Gaochuan; Wang, Yanping; Li, Shuqing; Wang, Baiyang; Chen, Zhihua; Zhu, Weifeng; Wang, Fei; Gan, Chun
Abstract: Background: Although the efficacy of antihypertensive drugs has been well established for primary hypertension, their effectiveness is always limited by side effects and poor compliance. Heat-sensitive moxibustion is an innovative acupoint stimulation therapy that is promising as a community health care intervention for hypertension. Aims: This study aims to evaluate the pragmatic effectiveness and safety of heat-sensitive moxibustion self-administration by patients in the community with primary hypertension. Methods: This study will adopt a multi-center, pragmatic, nonrandomized design. Six hundred patients with primary hypertension will be recruited from 4 communities. Each patient will choose to either receive heat-sensitive moxibustion self-administration + original antihypertensive drugs or maintain their original antihypertensive drugs without heat-sensitive moxibustion for 1 year. Expected outcomes: The primary outcome will be changes in systolic and diastolic blood pressures and the percentage changes in the doses of antihypertensive drugs. The secondary outcomes will be changes in quality of life assessed by a validated patient-reported outcome scale and the levels of fasting blood glucose, glycated hemoglobin, total cholesterol, triglycerides, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, urinary albumin, and serum creatinine. The proportion of patients with poor compliance with the heat-sensitive moxibustion regimen will also be evaluated as a secondary outcome. The safety of heat-sensitive moxibustion will be considered by analyzing the incidence of all and serious adverse events and their correlation with heat-sensitive moxibustion. Discussion: The findings of this study will provide pragmatic evidence for heat-sensitive moxibustion self-administration in patients in the community with primary hypertension and may also establish an ethical basis for further randomized controlled trials. Trial registration: The protocol of this trial was registered in ClinicalTrials.gov at May 11, 2020 (No. NCT04381520). Abstract : Supplemental Digital Content is available in the text